PENGARUH ELEVASI KAKI TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN DENGAN TINDAKAN ANESTESI SPINAL DI RSUD KOTA MATARAM - Dina Fithriana (Jurnal PRIMA, 2019)
Feet elevation is the position arrangement of where arranged undercarriage motion member on course is higher than the heart, so that blood return will mount because blood heaping at undercarriage motion member is not happened, so that degradation of blood pressure can be prevented. Extremities Elevation can give transfusion auto as much 400-500 ml blood so that vascular résistance of total periphery and blood pressure of mean artery descend. Hereinafter will there are dilatation of vena and venula periphery by blood pooling and can degrade to pour to return to heart so that can degrade to pour the heart and blood pressure degradation. Hypotension when taking place long time and not given therapy not will cause the hypoxia of network and organ. To know the influence of feet elevation to change blood pressure at patient with the action of anesthesia spinal in RSUD of Mataram City. This Research Design is done by using quasi experimental. Population in this research is all patient experiencing operation with the action of anesthesia spinal in RSUD of Mataram City. The sampling number in this research is 30 respondents. Data analysis result showed there is influence of feet elevation to change blood pressure at anesthesia spinal action in RSUD of Mataram City, this matter is showed by result of significance t-test of equal to t-count 2,045 with value = -6,8. In this research can be concluded that systolic and diastolic blood pressure is occurred the degradation, whereas this matter can be showed there is increasing of the heart efficiency working causing blood pressure degradation. In this case gift of anesthesia spinal by feet elevation as much once, more tent to result the change significant to the heart working efficiency causing blood pressure degradation.